Improving the Normative and Legal Framework for Organization of Official Statistics in Ukraine as Part of Implementing the Association Agreement between Ukraine and EU - Chervona, S. P.; Parfentseva, N. О. (Statistics of Ukraine, 2022)
The process of adaption of the national law to the law of EU in “Statistics” field and the effectiveness of its practical implementation in 2014–2020 in the two dimensions – harmonization of the Ukrainian law on statistics with the law of EU and harmonization of the national statistical methodology with the EU methodology – was investigated as part of the monitoring of the implementation of Association Agreement between Ukraine, on the one part, and the European Union, European Atomic Energy Community and their Member State, on the other part. The analysis revealed that the State Statistics Service of Ukraine had devoted considerable effort to the implementation of commitments fixed in the Association Agreement between Ukraine and EU in “Statistics” concerning these two dimensions. It includes the elaboration of draft Laws of Ukraine “Official Statistics” and “Amendments of Some Laws of Ukraine Regulating the Official Statistical Activties”, which have passed through all the necessary debate and hearings, but still have to be brought to consideration of the session of the Verkhovna Rada of Ukraine. It is stressed that to harmonize the national statistical methodology with the methodology of EU and carry out the tasks envisaged in the action plan for implementation of the Association between Ukraine and EU in the section “Statistics and Information Exchange”, approved by the decree of the Cabinet of Ministers of Ukraine, the State Statistics Service of Ukraine has elaborated and approved the methodological guidelines on organization of the official statistical observation “Uses and reserves of fuels”, the technique for assessment of the final energy consumption by households by purpose, based on methods of mathematical modelling, the methodological guidelines for the official statistical observation of the network and activities of education institutions, the methodological guidelines for making typology of agricultural producers, the technique for estimating the indicators of social exclusion and poverty by living conditions, the methodological guidelines on organization of the official statistical observation of tourists and one day visitors in the state border checkpoints (for incoming tourism), the methodological guidelines on organization of the official statistical observation of the activities of collective accommodation facilities. Also, the Program for the Official Statistics Development till 2023 has been elaborated. The further steps towards harmonization of the Ukrainian law on statistics and the national statistical methodology with the law and methodology of EU are outlined.